Keterampilan Manajemen Ekonomi, Pendidikan Era Digital, Tantangan dan Peluang di Era Digital - Nugraha Yusman, Fajar (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2024)
The digital era brings significant changes in the way business and the economy is run, requiring individuals to have adaptive and innovative economic management skills. In facing the digital era, education plays a crucial role in preparing individuals to face challenges and take advantage of existing opportunities. This research will analyze various literature sources that discuss the relationship between education and improving economic management skills in the digital era. By paying attention to existing literature, this research will identify various challenges faced in improving economic management skills through education, such as the lack of integration of technology in the curriculum, the inability to keep up with developments in the digital economy, and the lack of risk management skills in the digital era. On the other hand, this research will also explore the opportunities available through education in improving economic management skills in the digital era, such as integrating technology in learning, developing curricula that are responsive to digital economic trends, and improving risk management skills through education. By analyzing related literature, this research is expected to provide in-depth insight into the challenges and opportunities in improving economic management skills through education in the digital era. It is hoped that the results of this research can contribute to the development of effective educational strategies to prepare individuals to face the economic demands of the digital era.